Marketing Distributor Strategy PT. Dipa Puspa Labsains In Making Purchasing Decisions Needs Of Microbiology Laboratories At H. Adam Malik General Hospital in 2020 - sulastri sulastri (Jurnal Kajian Kesehatan Masyarakat, 2020)
Marketing distributor strategy which is carried out by PT. Dipa Puspa Labsains in making purchasing decisions needs of microbiology laboratories at H. Adam Malik General Hospital right now is in accordance with the supporting information from The Head of Microbiology Unit, Microbiology Analyst, The Head of Supporting Medical, Procurement and Supervisor Distributors by implementing Response Time, Product Variety, Product Availability, Customer Experience and Time to market strategies. User information which states that the increase in purchases of microbiology laboratory requirements in 2019 by 93.7% was caused by the instruments in the microbiology laboratory experiencing problems. Trouble requires confirmation with the company that supports the instrument to wait for confirmation that related to follow-up repairs, but it must follow a number of stages, the stage are the company receives a report from the user then with the guidance of a technician who supports the instrument by the user is asked to observe the troble section then find spare parts who experienced trouble, then found the accuracy between the companies that support the instrument with H. Adam Malik General Hospital that related to the indent time of the new spareparts. The indent time required is 2 to 3 months, thus the time for H. Adam Malik General Hospital which is a National Referral Hospital becomes an obstacle in microbiology laboratory services so that it requires making purchases that increase beyond the use of instruments. H. Adam Malik General Hospital continues to maintain Relationship with distributors to continue to provide maximum service. The research method used was qualitative research, with interview research design, and generaly, the marketing strategy of the laboratory distributor of PT. Dipa Puspa Labsains in making purchasing decisions needs of microbiology laboratories at H. Adam Malik General Hospital is correct